2023
DOI: 10.1007/s00464-022-09853-z
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted TAMIS: a systematic review of feasibility and outcomes

Abstract: Background In the advancement of transanal local excision, robot-assisted transanal minimal invasive surgery is the newest development. In the confined area of the rectum, robot-assisted surgery should, theoretically, be superior due to articulated utensils, video enhancement, and tremor reduction, however, this has not yet been investigated. The aim of this study was to review the evidence reported to-date on experience of using robot-assisted transanal minimal invasive surgery for treatment of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…In the present series 90% of patients had an R0 resection with two patients having a deep margin involved (< 1 mm). This shows that extending the indication beyond the 3 cm limit indicated by the NCCN guidelines [ 27 ] can be considered safe as proposed by other studies, therefore, tumour dimension should not necessarily be considered a contraindication [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In the present series 90% of patients had an R0 resection with two patients having a deep margin involved (< 1 mm). This shows that extending the indication beyond the 3 cm limit indicated by the NCCN guidelines [ 27 ] can be considered safe as proposed by other studies, therefore, tumour dimension should not necessarily be considered a contraindication [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
“…r-TAMIS allows for extending the height of dissection as shown in the current study with a median distance from the AV of 7.5 (5.0–11.7) cm and a maximal height of 15 cm. This allows the surgeon to expand the indication of transanal excision to the upper rectum and sigmoid which could further benefit from the use of endoscopic robotic platforms as the Flex® Colorectal Drive Robotic System (Medrobotics Corporation, Raynham, MA, USA) [ 10 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, the most frequent complication was peritoneal entry (2.1%); postoperative bleeding was reported in six (1.9%) patients, where three (0.9%) required endoscopic therapy [6, [10][11][12][13]. In particular, a prior study reported wound dehiscence in patients who received neoadjuvant chemoradiation [6].…”
Section: Discussionmentioning
confidence: 99%